2020
DOI: 10.1002/eng2.12280
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment classification of skewed shoppers' reviews using machine learning techniques, examining the textual features

Abstract: With the speedy growth of online shopping, it has become of crucial importance for product makers to analyze, and handle a wealth of products' reviews. However, such a high volume of reviews, along with a wide variety of opinions, makes it hard for manufacturers to know exactly how they can improve their products without having an efficient approach. For this purpose, the results of sentiment classification would help the customers to retrieve the necessary information to choose an appropriate product, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…In light of this, unstructured data from social media has increased the demand for sentiment analysis. The author in [13] explained that sentiment analysis could be at different levels, such as document level, sentence level, and aspect-based. The results of experimental studies [14] also showed that one of the tasks of sentiment classification at the document level is to consider the importance of sentences.…”
Section: A Tourist Place Reviews Sentiment Classificationmentioning
confidence: 99%
“…In light of this, unstructured data from social media has increased the demand for sentiment analysis. The author in [13] explained that sentiment analysis could be at different levels, such as document level, sentence level, and aspect-based. The results of experimental studies [14] also showed that one of the tasks of sentiment classification at the document level is to consider the importance of sentences.…”
Section: A Tourist Place Reviews Sentiment Classificationmentioning
confidence: 99%
“…After applying the Grid Search algorithm to the TF-IDF vectorizer implemented in the Scikit learn Python package [53], the TF-IDF character (1,7) grams feature set and maximum features of 5000 has been chosen for optimal Amharic sentiment classification. For several NLP applications, the TF-IDF character level n-grams feature outperforms the word-level grams feature, according to the literature [25,29,54]. Specifically, character n-grams features outperform word grams features for dealing negation in Amharic sentiment classification [22].…”
Section: Proposed Stacking Algorithmmentioning
confidence: 99%
“…(3) Base Learner Algorithms: Support Vector Machine (SVM), Naive Bayesian (NB), and Random Forest (RF) are the most commonly used supervised machine learning algorithms in NLP [54,56], and they were chosen for Amharic sentiment classification in this study. For the sake of simplicity and comparison, we choose Logistic Regression (LR) as a meta-learner for combining the base learners.…”
Section: Proposed Stacking Algorithmmentioning
confidence: 99%
“…But, the designed method failed to achieve higher prediction accuracy. Several machine learning approaches were designed in [14] for Sentiment classification using examining the reviews. A novel pattern-based method was introduced in [15] for aspect extraction and sentiment analysis with higher accuracy.…”
Section: Literature Reviewmentioning
confidence: 99%